So sometimes we write x instead of x y and we write

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = X + Y. Solution: We have fS = fX ∗ fY , and we will use Figure 4.15 to help work out the integral in (4.16). As shown, the graph of the function fY (c − u) is a rectangle over the interval [c − 1, c]. f (u) f (c!u) fX (u) X Y f (c!u) Y u c !1 0 c u c !1 1 0 1 c Figure 4.15: Calculating the convolution of two rectangle functions. To check this, note that if u = c then fY (c − u) = fY (0), and as u decreases from c to c-1, c − u increases from zero to c, so fY (c − u) = 1 for this range of u. The product fX (u)fY (c − u) is equal to one on [0, 1] ∪ [c − 1, c] and is equal to zero elsewhere. As shown in Figure 4.15, if 0 < c ≤ 1, then the overlap is the interval [0, c], and therefore fX ∗ fY (c) = c. If 1 < c < 2, the overlap is the interval [c − 1, 1] which has length 2 − c, and therefore fX ∗ fY (c) = 2 − c. Otherwise, the value of the convolution is zero. Summarizing, 0<c≤1 c 2−c 1<c≤2 fS (c) = 0 else. so the graph of fS has the triangular shape shown in Figure 4.16. f (c) S 1 c 0 1 2 Figure 4.16: The convoluti...
View Full Document

Ask a homework question - tutors are online